2020
DOI: 10.3390/molecules25020336
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and 2-Dimensional Correlation Spectroscopy Study of the Effect of CH3NH3PbI3 and CH3NH3SnI3 Photovoltaic Perovskites on Eukaryotic Cells

Abstract: We studied the effect of the exposure of human A549 and SH-SY5Y cell lines to aqueous solutions of organic/inorganic halide perovskites CH3NH3PbI3 (MAPbI3) and CH3NH3SnI3 (MASnI3) at the molecular level by using Fourier transform infrared microspectroscopy. We monitored the infrared spectra of some cells over a few days following exposure to the metals and observed the spectroscopic changes dominated by the appearance of a strong band at 1627 cm−1. We used Infrared (IR) mapping to show that this change was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The results indicated that the higher concentration of perovskite material inside the cell medium, the lower cell viability rate observed. [ 58 ] As mentioned above, the role of B‐site Pb 2+ cation was replaced by the NH 4+ cation in MDABCO‐NH 4 I 3 to reduce toxicity, as illustrated in Figure 5 a . To further assess the cytotoxicity of the as‐synthesized MDABCO‐NH 4 I 3 film, a cell viability test has been conducted by using L929 fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the higher concentration of perovskite material inside the cell medium, the lower cell viability rate observed. [ 58 ] As mentioned above, the role of B‐site Pb 2+ cation was replaced by the NH 4+ cation in MDABCO‐NH 4 I 3 to reduce toxicity, as illustrated in Figure 5 a . To further assess the cytotoxicity of the as‐synthesized MDABCO‐NH 4 I 3 film, a cell viability test has been conducted by using L929 fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…6 The two peaks are typically assigned to the Amide I and Amide II modes of the amide group of polypeptide chains, although some amino acid side chains, lipids and other molecules can also contribute. 43 One difference from cellular far-field spectra, and from protein spectra in general, is the relative intensity of the two peaks. This is comparable in Figure 5C, while in far-field IR spectra the Amide I peak is markedly more intense than the Amide II peak.…”
Section: Figure 4 Ptir Images Of the Cellular Surface Of Buccal Cells...mentioning
confidence: 99%
“…24−26 1, low-dimensional perovskite structures are preferably formed. 21,27,28 Some organic cations with a large size, such as phenethylammonium (PEA + ), 11,29 ethylenediammonium (EDA 2+ ), 15 butylammonium (BA + ), 30,31 and allylammonium (ALA + ), 32 have been introduced to replace A cation to make efficient Sn PSCs. Li et al added PEACl into FASnI 3 to suppress the oxidation of Sn 2+ and induce perovskite crystallization perpendicular to the substrate, achieving a power conversion efficiency (PCE) of 9.1%.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The substitution of organic cations or halogen anions are effective to improve the performance of Sn-based PSCs. Although there are no convenient rules to guide the selection of organic salts, the structural stability of perovskites is the primary consideration. Typically, the perovskite (ABX 3 ) with a Goldschmidt tolerance factor approaching 1, determined by the size of A cation and the interaction between A cation and BX 6 octahedra, can obtain a relatively stable structure. If the tolerance factor is beyond 1, low-dimensional perovskite structures are preferably formed. ,, …”
Section: Introductionmentioning
confidence: 99%